Pengembangan Sistem Monitoring Proses Distribusi Tomat Menggunakan Internet of Things (IoT) - Ida Bagus Suryaningrat; Adam Hegi Darmawan; Winda Amilia; Bertung Suryadharma (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
Technological developments are used to provide product quality assurance and provide goods and services to consumers. Product quality is a condition related to the product, where the product could meet the needs and satisfaction of consumers. Product quality assurance, could be supported from raw materials, processes to distribution. This condition requires a tool that is able to control or monitor agricultural products by utilizing technology, namely the Internet of Things (IoT) using temperature, humidity, vibration, carbon dioxide (CO2) sensors and GPS that is able to show the location when the distribution process takes place in real time. The purpose of this study was to design and performance monitoring tools for temperature, humidity, vibration, carbon dioxide (CO2) and location during the distribution process. The results of the field test showed that the GPS sensor was able to show the location in real time according to the delivery route. The results of recording the highest temperature data was 30.8°C and the lowest temperature was 27.8°C, while the lowest humidity was 80% RH and the highest was 94% RH. The recording results from the SW-420 sensor showed that 51.04% for small vibration, 19.79% for medium vibration, and 28.64% for large vibration. The recording results from the MQ-2 sensor was able to show the carbon dioxide value around the tomatoes, with the lowest carbon dioxide with the value of 10% and the highest with the value of 23%.